Knowledge, Attitude and Preventive Practices of Dengue in Local Community People of Janakpurdham - Yadav, Khushbu; Yadav, Nagendra; Prakash, Satyam; Yadav, Basant Kumar (Janaki Medical College Journal of Medical Science, 2022)
Background & Objective: Dengue is an acute febrile disease, caused by dengue virus transmitted by the female aedes mosquito. The objective of this study was to access the knowledge, attitude, and preventive practices of local community people with regard to dengue viral infection. Material and Methods: This descriptive cross-sectional study was conducted in the month of August 2022 in Janakpurdham, Nepal. A total of 363 participants were enrolled. Convenient non-random sampling method was applied by designing a standard structured questionnaire. Data was entered in SPSS 18 and p-value<0.05 was considered as statistically significant. Results: The majority of study participants (98.63%) were aware of dengue infection. Overall, 79.62% of respondents were aware that an aedes mosquito bite can cause dengue. About 68.04% of the participants expressed fear of acquiring dengue, and 82.09% agreed that it is a serious illness. Only 25.06% of participants used a coil or electrical insect repellent. The usage of smoke and fans to ward off mosquitoes was significantly correlated with gender (p<0.05). Conclusion: The study concludes that the community people’s knowledge, attitude, and preventive activities were satisfactory. Various preventive management strategies as well as a public awareness campaign should be used on a regular basis to control the vector.